SP8.1.6 The role of staging imaging prior to neo-adjuvant chemotherapy (NACT) for breast cancer. (28th October 2021) - Muir, Duncan; Gathani, Toral; Dodwell, David; Remoundos, Dennis
Abstract: Aims: The Royal College of Radiologists (RCR) guidelines state that there is no evidence base for routine imaging in patients with early breast cancer (≤T2 and ≤N1 disease) planned for NACT. Standard practice in our unit is to routinely stage all patients scheduled for NACT with CT chest/abdomen/pelvis and MRI marrow. Our aim was to assess the utility of this practice in this group of patients. Methods: All patients who received NACT for breast cancer from 2017 to 2020 were included. The imaging reports were reviewed to identify whether metastatic disease had been detected, or further investigations were required. Results: 127 patients were identified. 51 patients met the current RCR criteria for imaging and were excluded. Of the remaining 76 patients with ≤T2 and ≤N1 disease, metastatic disease was found in 13. This was detected by CT in 9 patients, by MRI in 1 patient, and by both modalities in 3 patients. Indeterminate findings requiring further investigation were present in 17 with 6 patients requiring at least one further scan. Conclusion: Routine staging investigations detected metastatic disease in almost one in five patients with early breast cancer about to start NACT, impacting on their treatment planning. A similar proportion of patients required further investigations due to indeterminate findings. We believe that routine staging using our current criteria for NACT patients should continue. In the absence of evidence from prospective trials, there is a need for ongoing audit of the utility of systemic staging in early breast cancer.